O conceito de saber escolar clássico em Dermeval Saviani: Implicações para a Educação Matemática - Giardinetto, José Roberto Boettger [UNESP] (My University, 2010)
The aim of this paper is initially to consider some issues related to the relationship between humanization and alienation in the process of historical social development of human gender. These considerations are fundamental for understanding the concept of classical in Dermeval Saviani and the consequences for research about the historical development of Mathematics currently found in school curriculums. The intention is to value the appropriation of school mathematics as a humanizing element that becomes accessible through the activity of teaching.
The concept of the classical school knowledge in Dermeval Saviani: Consequences for Mathematics Education
Keywords: Historical-critical pedagogy; History of mathematics; Marxism; School math